Acceleration of Lipid Accumulation in Oleaginous Diatom Navicula sp. Under Nitrogen Limitation - Karthick Murugan, Palanisamy; Karthiani, Kanagesan; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan; Gaanty Pragas, Maniam (Faculty of Agricultural Science and Forestry, Universiti Putra Malaysia Bintulu Sarawak Campus, 2021)
Diatom biomass gain attention globally as a source of lipid due to their high growth rate and biomass composition which can compete with fossil fuel for biodiesel production. Accumulations of natural lipid can be enhanced by various stress factors in diatoms. In this study, the effect of different nitrogen concentration on biomass and lipid production was investigated by cultivation of oleaginous diatom Navicula sp. for biodiesel production. The cultivation performed in phases where initially the culture was cultured in standard media for seven day and followed in different concentration of nitrogen such as limitation (0.35 mM), standard as media (1.76 mM), Repletion (3.5 mM) and free of nitrogen (0 mM) as second phase for eight days. The cells were grown under light intensity of 150 μmol photon m-2s-1(12:12 h day: light period) temperature (21±1 °C). Diatom Navicula sp. Showed highest growth and biomass production (734±15 mg/L) in nutrient f/2 standard media and extracted 19% of lipid. However, 24% of lipid yield was extracted which is significantly high from the biomass (528±10 mg/L) cultured in limited nitrogen media. Nitrogen limitation enhanced the fatty acid as saturated fatty acid C16:0, unsaturated fatty acid C16:1 and polyunsaturated fatty acid C18:3. Navicula sp., have potential to accumulate lipid in nitrogen limitation condition biodiesel production.